2018
DOI: 10.1080/03009734.2018.1489918
|View full text |Cite
|
Sign up to set email alerts
|

Desloratadine and depression, a drug safety signal based on worldwide spontaneous reporting of side effects

Abstract: Objective: Desloratadine, a third-generation antihistamine, is claimed to cause fewer central nervous system (CNS) adverse drug reactions (ADRs) than antihistamines of the first- and second-generation. While literature is inconclusive regarding the possible CNS effects, symptoms like somnolence and hallucinations are acknowledged ADRs of desloratadine, indeed suggesting some passage of this drug across the blood–brain barrier. Depression is currently not described as an ADR in the approved desloratadine produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“… 39 A third-generation antihistamine, desloratadine, was reported to cause fewer adverse drug reactions in the central nervous system than first- and second-generation antihistamines. 40 In this study, the direct binding between the NMT1 protein and desloratadine was confirmed by SPR analysis and molecular docking simulation, and Asn-246 in NMT1 was identified to play a crucial role in the binding of NMT1 to desloratadine. We first found that desloratadine can inhibit the proliferation, migration and invasion of HCC cells.…”
Section: Discussionsupporting
confidence: 54%
“… 39 A third-generation antihistamine, desloratadine, was reported to cause fewer adverse drug reactions in the central nervous system than first- and second-generation antihistamines. 40 In this study, the direct binding between the NMT1 protein and desloratadine was confirmed by SPR analysis and molecular docking simulation, and Asn-246 in NMT1 was identified to play a crucial role in the binding of NMT1 to desloratadine. We first found that desloratadine can inhibit the proliferation, migration and invasion of HCC cells.…”
Section: Discussionsupporting
confidence: 54%
“…Loratadine, treated as drug positive group and is used in the treatment of AR [9]. However, long-term or high-dosage use of loratadine in AR can cause undesirable side effects, for example anaphylactic reactions [26] and sedation [27]. HE had a therapeutic activity for AR, and a higher HE concentration had a better therapeutic effect on AR.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, a significant proportion of patients do not achieve sustained remission, despite serial treatments [ 5 ]. Clinical practice has proven that many chemical drugs have beneficial therapeutic effects in depression, but they are also associated with adverse reactions, such as drowsiness and dystonia, and have shortcomings, such as a narrow antidepressant spectrum and a high rate of relapse [ 6 ].…”
Section: Introductionmentioning
confidence: 99%